(untitled) (Journal of Parents and Teachers, 2014)
Using a blog in arts and crafts class allows us not only to bring new technologies closer to arts and crafts, but also to trace the classes, open the doors of the class and share didactic units, online resources, innovative experiences and anything we could imagine.